Drug-induced psoriasis - Sunil Dogra; Divya Kamat (Indian Journal of Rheumatology)
Psoriasis is known to be triggered by a number of factors including drugs. Some therapeutic agents for the treatment of psoriasis are also known to have a paradoxical effect and alter the course of the disease. The drugs may either cause de novo psoriasis or are responsible for aggravating preexisting psoriasis. The distinction is not always clear-cut and is clinically often indistinguishable from psoriasis vulgaris. The morphological types can vary from plaque psoriasis to pustular psoriasis and even erythroderma. There are certain established agents which are known to trigger psoriasis. Many of the biological agents and targeted therapies available today can trigger psoriasis by activating signaling pathways. The lag time between the intake of drug and onset of psoriasis is highly variable and thus requires a high index of suspicion. Due to the various systemic comorbidities, patients with psoriasis often receive polypharmacy and hence it is important for dermatologists, rheumatologists, and physicians to be aware of the possible triggers.